PENGARUH RETURN ON ASSET, RETURN ON EQUITY, EARNING PER SHARE, DEVIDEN PAYOUT RATIO DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDOENSIA TAHUN 2013-2015 - Pradita Astari Pratiwi, 14.05.51.0027; Sudarsi, Sri (Students' Journal of Economic and Management, 2018)
The purpose of this research is to know the effect of return on asset, return on equity, earnings per share, dividend payout ratio and capital structure to stock price. The sample of this are manufacture company listed in BEI period 2013-2015 with 468 companies using purposive sampling method. Multiple linear regression analysis is used to analyze by SPSS program. The results of this study prove partially that the return on asset and earnings per share have a positive and significant effect on stock prices, while return on equity, dividend payout ratio and capital structure have no effect and not significant to stock prices. Simultaneously proves that return on asset, return on equity, earnings per share, dividend payout ratio and capital structure have significant effect to stock price. Adjusted R Square value shows the result of share price is influenced by return on asset, return on equity, earnings per share, dividend payout ratio and capital structure, while the rest is followed by other variables outside this research. Keywords :Return On Asset, Return On Equity, Earning Per Share, Deviden Payout Ratio dan Capital Structure.